Renal artery stenosis and aneurysm in a child presenting with hypokalemia, metabolic alkalosis and hypertension [Hipokalemi, metabolik alkaloz ve hipertansiyon ile bavuran bir çocukta renal arter darliǧi ve anevrizmas] - ALPAY, HARİKA; GÖKCE, İBRAHİM; YILDIZ, NURDAN (Turkish Society of Nephrology, 2016)
Renovascular hypertension is one of the important causes of secondary hypertension in children and can be caused by many different diseases, with the most common being fibromuscular dysplasia (FMD) and Takayasu arteritis (TA). The differential diagnosis between TA and FMD seems to be difficult and much less certain than is generally assumed in many cases. Here we present a case report of an 11-yearold girl with FMD presenting with hypokalemia, metabolic alkalosis and hypertension secondary to renal artery stenosis and hyperreninemic hyperaldosteronism.
Keywords: Hypokalemia; Metabolic alkalosis; Renovascular hypertension